ANALYSIS OF THE ECONOMIC AND SOCIAL CONSEQUENCES OF THE DEVELOPMENT OF THE DIGITAL ECONOMY IN THE REPUBLIC OF UZBEKISTAN (Marketing Journal, 2025)
This article analyzes the economic and social consequences of implementing and developing the digital economy in the Republic of Uzbekistan. Changes arising from 162 state-adopted digitization strategies, e -government, digital services, and initiatives to automate business processes are examined. The article evaluates the impact of digital technologies on labor market transformations, job dynamics, employment, and the education system, as well as changes in business efficiency indicators. Both positive and potentially negative effects of the digital economy are presented in a balanced manner. Special attention is given to issues related to digital inequality, levels of digital literacy, regional disparities, and information security. The author proposes recommendations aimed at ensuring sustainable growth in the development of the digital economy.
Keywords: digital economy; social consequences; economic analysis; digitization; digital transformation; Uzbekistan; labor market; digital inequality